Intra‐arterial injection of lidocaine into middle meningeal artery to treat intractable headaches and severe migraine. Issue 6 (13th August 2021) - Qureshi, Adnan I.; Pfeiffer, Kimberley; Babar, Sehar; Huang, Wei; Lobanova, Iryna; Ishfaq, Muhammad F.; French, Brandi R.; Siddiq, Farhan; Gomez, Camilo R.
Abstract: Background and Purpose: We report the results of intra‐arterial injection of lidocaine in the middle meningeal artery in patients with intractable headache or status migrainosus. Methods: We treated four patients with intra‐arterial lidocaine (2 mg/ml) in doses up to 50 mg in each middle meningeal artery via a microcatheter bilaterally (except in one patient). In two patients with intractable headache, the daily maximum intensity of headache (graded by 11‐point numeric rating scale) was recorded for 7 days postprocedure. In two patients with status migrainosus, migraine‐related disability 3 months prior and after treatment using MIDAS (Migraine Disability Assessment) questionnaire was recorded. Results: Intra‐arterial lidocaine reduced the headache intensity from 8/10 and 10/10 to 0/10 in the two patients with intractable headaches for 2 days (day 0 and day 1) postprocedure. Despite recurrence of headache on day 2, the intensity was less than preprocedure intensity up to the last day recorded (by 3 and 2 points on day 7). In the two patients with status migrainosus, there was immediate reduction in headache intensity following intra‐arterial lidocaine. The post treatment 3‐month MIDAS score was lower in both patients compared with pretreatment 3‐month score; 3 versus 30 and 55 versus 90. Severe disability preprocedure by MIDAS was reduced to little or no disability postprocedure in one patient. Conclusions: Intra‐arterial lidocaine resulted in amelioration of headache in patients with intractable headache and those with status migrainosus with improvement lasting longer than the short half‐life of lidocaine possibly related to central desensitization.